Genome-wide identification and characterization of 14-3-3 gene family related to negative regulation of starch accumulation in storage root of Manihot esculenta - Pan, Ranran; Wang, Yajie; An, Feifei; Yao, Yuan; Xue, Jingjing; Zhu, Wenli; Luo, Xiuqin; Lai, Hanggui; Chen, Songbi (Frontiers in Plant Science, 2023)
The 14-3-3 protein family is a highly conservative member of the acid protein family and plays an important role in regulating a series of important biological activities and various signal transduction pathways. The role of 14-3-3 proteins in regulating starch accumulation still remains largely unknown. To investigate the properties of 14-3-3 proteins, the structures and functions involved in starch accumulation in storage roots were analyzed, and consequently, 16 Me14-3-3 genes were identified. Phylogenetic analysis revealed that Me14-3-3 family proteins are split into two groups (ε and non-ε). All Me14-3-3 proteins contain nine antiparallel α-helices. Me14-3-3s-GFP fusion protein was targeted exclusively to the nuclei and cytoplasm. In the early stage of starch accumulation in the storage root, Me14-3-3 genes were highly expressed in high-starch cultivars, while in the late stage of starch accumulation, Me14-3-3 genes were highly expressed in low-starch cultivars. Me14-3-3 I, II, V, and XVI had relatively high expression levels in the storage roots. The transgenic evidence from Me14-3-3II overexpression in Arabidopsis thaliana and the virus-induced gene silencing (VIGS) in cassava leaves and storage roots suggest that Me14-3-3II is involved in the negative regulation of starch accumulation. This study provides a new insight to understand the molecular mechanisms of starch accumulation linked with Me14-3-3 genes during cassava storage root development.